The Effect of Non-Performing Financing and Financing to Deposit Ratio on Capital Adequacy Ratio in Sharia Commercial Banks in Indonesia - Enjeli Femi Soviani; Haqiqi Rafsanjani; Tiara Anindya Virana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Capital Adequacy Ratio (CAR) in Sharia Commercial Banks in Indonesia, both in the short and long term. The main problem studied is how financing risks and the effectiveness of intermediation affect the capital resilience of Islamic banks in the midst of financial industry dynamics. This study uses a quantitative approach with an associative design and time series data for the 2018–2024 period sourced from the publication of the Financial Services Authority (OJK). The analysis methods used included ADF stationarity test, optimal lag test, VAR stability test, Granger causality test, Johansen cointegration test, and Vector Error Correction Model (VECM) estimation, which was complemented by Impulse Response Function (IRF) and Variance Decomposition (VD) analysis. The results showed that all variables were stationary at the first difference level and there were three cointegration relationships, which indicated a long-term relationship between variables. The VECM estimate shows that NPF has a negative and significant effect on CAR in the long term, while FDR has no significant effect on either the short or long term. Granger's causality test found a one-way relationship from CAR to NPF, while the relationship between FDR and CAR was insignificant. These findings indicate that the strengthening of Islamic banks' capital is more influenced by the quality of financing than the intermediation function. This research contributes empirically in enriching the literature on Islamic banking stability and provides policy implications for regulators and bank management in prioritizing financing risk control to maintain sustainable capital adequacy.